An investigation into the determinants of the South African unemployment rate, 1970-2002 - Schoeman, Christie; Blaauw, Derick; Pretorius, Anmar (Acta Academica: Critical views on society, culture and politics, 2008)
From 1970 to 1977 unemployment in South Africa oscillated around a near-constant mean. Since 1983 unemployment has shown a definite upward trend defying the existence of a long-run natural rate. South African unemployment data exhibits signs of hysteresis, suggesting that long-run unemployment is endogenously determined. Empirical results confirm that the total fixed capital stock, interest rate and degree of unionisation of the labour force are important factors in explaining the unemployment rate in South Africa. This implies that long-run equilibrium unemployment in South Africa is endogenously determined by economic as well as institutional factors.